The Influence of Digital Banking Transactions and Third-Party Funds on Fee Based Income Sharia Commercial Banks in Indonesia - Nofinawati, Nofinawati; Nasution, Adanan Murroh; Panggabean, Apriani (Journal of Islamic Financial Technology, 2025)
The instability of profit-sharing income in Islamic banks, driven by rising non-performing loans, strict regulations, and rapid financial technology development, has encouraged banks to explore alternative income sources such as Fee Based Income (FBI). This study aims to examine the influence of Digital Banking transactions and Third Party Funds (DPK) on Fee Based Income in Islamic Commercial Banks during 2019–2023. A quantitative approach was applied using secondary data from 60 monthly financial reports published by the Financial Services Authority (OJK). The analysis involved descriptive statistics, classical assumption tests, hypothesis testing, multiple linear regression, and the coefficient of determination using SPSS 24. The results show that Digital Banking has no significant partial effect on Fee Based Income, while Third Party Funds have a significant and positive effect. However, both variables jointly influence Fee Based Income significantly. These findings suggest that while digital banking adoption alone may not directly increase service-based income, the availability of third-party funds plays a crucial role. This implies that Islamic banks should optimize fund mobilization and enhance fee-based services to strengthen financial stability.